Julian of Toledo, Prognosticum futuri saeculi – Foreknowledge of the world to come, transl. and introd. by Tommaso Stancati OP, Foreword by card. Antonio Cañizares Llovera, Ancient Christian Writers 63, New York – Mahwah 2010, The Newman Press, pp.608 - Degórski, Bazyli (Vox Patrum, 2011)
nie dotyczy